Euthanasia requests, procedures and outcomes for 100 Belgian patients suffering from psychiatric disorders: a retrospective, descriptive study - Thienpont, Lieve (BMJ Open, 2015)
OBJECTIVES: To identify patterns in euthanasia requests and practices relating to psychiatric patients; to generate recommendations for future research. DESIGN: Retrospective analysis of data obtained through medical file review. SETTING: Outpatient psychiatric clinical setting in the Dutch-speaking region of Belgium, between October 2007 and December 2011; follow-up at the end of December 2012. PARTICIPANTS: 100 consecutive psychiatric patients requesting euthanasia based on psychological suffering associated with psychiatric disorders (77 women, 23 men; mean age 47 years; age range 21–80 years). MAIN OUTCOME MEASURES: Patient sociodemographic characteristics; diagnoses; decisions on euthanasia requests; circumstances of euthanasia procedures; patient outcomes at follow-up. RESULTS: Most patients had been referred for psychiatric counselling by their physician (n=55) or by LEIF (Life End Information Forum) (n=36). 90 patients had >1 disorder; the most frequent diagnoses were depression (n=58) and personality disorder (n=50). 38 patients required further testing and/or treatment, including 13 specifically tested for autism spectrum disorder (ASD); 12 received an ASD diagnosis (all Asperger syndrome). In total, 48 of the euthanasia requests were accepted and 35 were carried out. Of the 13 remaining patients whose requests were accepted, 8 postponed or cancelled the procedure, because simply having this option gave them enough peace of mind to continue living. In December 2012, 43 patients had died, including 35 by euthanasia; others died by suicide (6), palliative sedation (1) and anorexia nervosa (1). CONCLUSIONS: Depression and personality disorders are the most common diagnoses in psychiatric patients requesting euthanasia, with Asperger syndrome representing a neglected disease burden. Further research is needed, especially prospective quantitative and qualitative studies, to obtain a better understanding of patients with psychiatric disorders who request euthanasia due to unbearable psychological suffering.